Forging ahead from adaptations of teaching during the COVID‐19 pandemic: Perspectives from multiple pharmacy programs. Issue 1 (15th November 2020) - Higbea, Ashley; Bald, Elizabeth; Isaacs, Alex N.; Richter, Sara K.; Stamm, Pamela L.; Kassel, Lynn E.
Abstract: The introduction of the coronavirus disease 2019 (COVID‐19) pandemic in the Spring semester of 2020 sent many educational units, elementary to higher education, scrambling to move content to remote learning. Within a professional program, this push highlighted gaps or potential pitfalls in preparing students to enter the health care field. This article highlights lessons learned in remote teaching during the pandemic from six unique colleges and schools of pharmacy: Auburn University, Drake University, Purdue University, University of Health Sciences and Pharmacy in St. Louis, Texas Tech University Health Science Center, and University of Utah. These lessons learned pertain to remote content delivery, student engagement, skill development, and assessments within the classroom and experiential settings. Within the classroom setting, the challenges, literature, personal experiences, and key recommendations for lecture‐based learning, group‐based learning, lab‐based learning, and assessments are described. Similarly, for the experiential setting, the challenges, literature, personal experiences, and key recommendations are also described, including training learners for remote patient care as well as examples for remote experiential activities and assessment. Forging ahead, there will be a continued need for future research for remote learning within pharmacy education.